A Collaborative Rapid Response to Abuse in U.K. Gymnastics Using Group Focused Acceptance and Commitment Therapy-Based Program - Misia Gervis; Lara Baker-Power; Aura Goldman; James Mackenzie (Journal of Clinical Sport Psychology, 2025)
Although abuse is commonplace within sport, the abuse scandal in gymnastics has left many current and ex-gymnasts traumatized by their experiences. When the scandal emerged, we recognized an immediate need for support for survivors of this abuse within British Gymnastics; this paper documents our response. This paper presents practice-based evidence on how a focused acceptance and commitment therapy-based intervention program was designed and delivered to four different groups: parents/guardians, older ex-gymnasts, adolescent gymnasts (13–18 years), and younger gymnasts (9–12 years). In total, 90 individuals attended the group sessions across a period of 7 months. The intervention was found to be helpful in helping the group members to overcome current and historical traumas resultant from their experiences in gymnastics. The group program was efficacious in establishing psychological safety, imparting acceptance and commitment therapy-based skills, improving family relationships, and providing a healing group experience.